2016
DOI: 10.1007/s11926-016-0592-x
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia in Chronic Pain Disorders

Abstract: This review proposes a critical discussion of the recent studies investigating the presence of alexithymia in patients suffering from different chronic pain (CP) conditions. The term CP refers to pain that persists or progresses over time, while alexithymia is an affective dysregulation, largely observed in psychosomatic diseases. Overall, the examined studies showed a high prevalence of alexithymia, especially difficulties in identifying feelings, in all the different CP conditions considered. However, the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
59
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 57 publications
(38 reference statements)
3
59
2
5
Order By: Relevance
“…With regard to the first aim of this study, the results showed significantly higher scores on alexithymia (i.e., TAS‐20 total, DIF and EOT factors scores) in our group of FM patients compared to the Italian normative data (Bressi et al ., ). These results confirm previous studies evaluating the prevalence of alexithymia in FM patients, highlighting impairments in the recognition of their own emotions (Di Tella & Castelli, ; Ghiggia, Romeo, Tesio et al ., ; Sayar et al ., ; Steinweg et al ., ).…”
Section: Discussionsupporting
confidence: 92%
“…With regard to the first aim of this study, the results showed significantly higher scores on alexithymia (i.e., TAS‐20 total, DIF and EOT factors scores) in our group of FM patients compared to the Italian normative data (Bressi et al ., ). These results confirm previous studies evaluating the prevalence of alexithymia in FM patients, highlighting impairments in the recognition of their own emotions (Di Tella & Castelli, ; Ghiggia, Romeo, Tesio et al ., ; Sayar et al ., ; Steinweg et al ., ).…”
Section: Discussionsupporting
confidence: 92%
“…Таким образом, биопсихосоциальная модель становится наиболее полным подходом к изучению и пониманию хронической боли. Отмечается тесное взаимодействие биологических, психологических и социальных факторов в клинических проявлениях боли [3].…”
unclassified
“…Среди психологических расстройств алекситимия, представляющая собой функциональную особенность нервной системы индивида, может способствовать появлению и усилению болевой симптоматики [3]. Алекситимия в различных ее проявлениях встречается у 5-25 % условно здоровых людей, а у пациентов с хронической болью она появляется в 47%.…”
unclassified
See 1 more Smart Citation
“…Alexithymia has been found in patients suffering chronic pain with no identifiable cause, including patients with fibromyalgia (van Middendorp et al, 2008), depression and psychosomatic illnesses (Kusevic et al, 2013), high blood pressure, Crohn's disease, psychiatric patients (panic and anxiety disorders, depression), and those with kidney and rheumatic diseases (Marchesi et al, 2013;Sayar, Kirmayer, & Taillefer, 2004;Silva, Freitas, Moreira, Santos, & Almeida, 2016;Di Tella & Castelli, 2016). However, the prevalence of alexithymia has also been found to be as high as 7% among the general population (Steinweg, Dallas, & Rea, 2011) without any link to specific disorders (Cox, Kuch, Parker, Shulman, & Evans, 1994;Praceres et al, 2000;Yoshida, 2000Yoshida, , 2007.…”
mentioning
confidence: 99%